IMPLEMENTASI PERMAINAN SAINS GEOMETRI PADA ANAK USIA DINI - Thezy Meilevia WIjayanti; Yasifa Arkanasya Ummayah; Lily Fitriani (ENTINAS: Jurnal Pendidikan dan Teknologi Pembelajaran, 2024)
To create interesting learning, of course, you need to apply learning while playing. It is not an easy thing to implement this, it must be done by understanding the characteristics of the child. The approach to this research is qualitative while the type of research is a case study. Data collection methods in this research are observation, interviews and documentation. According to Miles and Huberman, the steps in analyzing data are through data collection, data reduction, data presentation and conclusions. The results of this research are to understand the positive impact and effectiveness of using geometric science games in forming an understanding of geometry at this stage of development. It is hoped that the results of this research can contribute to the development of learning methods that are more innovative and appropriate to the characteristics of early childhood development.